Integration of Love-Based Curriculum and Deep Learning in Madrasahs: A Holistic Approach to Islamic Education - Syafaruddin, Baso; Sarda, Muh; Mawaddah, Nurul; Agustinanda, Baso (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Islamic education at madrasahs still struggles to balance spiritual and emotional qualities like love for Allah, the Prophet, and others with 21st-century skills like analytical and problem-solving. Curricula generally emphasize cognitive without truly integrating emotive and use AI technologies for tailored learning. Thus, this article proposes a holistic curriculum integration model in Madrasahs that combines love-based education (a moral and spiritual foundation) with deep learning technology (a tool for personalization and cognitive acceleration) to create noble and competitive students. This study is descriptive, qualitative, and literature reviewed. An in-depth analysis of Islamic curriculum theory, love-based education, and deep learning in education yielded data. Synthesizing the analysis results created an integration model conceptual framework. A love-based core curriculum (values of compassion, ethics, and spirituality are embedded in every subject), deep learning as an enabler (algorithms analyze students' learning styles, pace of understanding, and emotional/spiritual needs to personalize materials and interventions), and a holistic learning environment are the three pillars of the proposed integration model. This strategy promises to boost student engagement, cognitive learning, and Islamic character. This article offers a framework that integrates spiritual/affective and technological/cognitive aspects to advance Islamic education curriculum thinking. This page helps policymakers, curriculum creators, and Madrasah educators create a balanced, relevant, and adaptable educational approach.